Nutrition analysis of fermented okara, Glycine max and its effect on growth performance of Syrian hamster, Mesocricetus auratus - Nur Farihah Rani (2016)
This study is conducted to study the effect of feeding fermented okara on the growth performance of Syrian Hamster, Mesocricetus Auratus. Okara, soymilk residue was characterized and used as a supplement to enrich dietary ﬁbre and protein in the hamsters. Okara comprised 49% total dietary ﬁbre, of which only 0.55% was soluble. protein (33.4%), fat (19.8%), and ash (3.5%). Due to its high ﬁbre content and high protein and low production costs. okara is a good raw material and rich source for preparing ﬁbre and could also be used as a dietary supplement to prevent diabetes, obesity, and hyperlipidemia. Fermentation can increase the content of soluble ﬁbre of okara, which improves its nutritional quality and processing properties.Fennentation of okara is testing its microbial population by microbial analysis includes total plate count. total yeast count. total mould count and total lactic acid bacteria count. The results can determine whether it is safe to be consuming by animals or not. Lactic acid bacteria are the most commonly used microorganism for processing of feeds. The effectiveness of fermented okara is continued testing by feeding to the Syrian Hamster, Mauratus. The Mauratus were procured and randomly distributed in two different treatments with three replicates. Each replicate has one Mauratus in the aquarium. Weight gain, feed conversion ratio (FCR) and speciﬁc growth rate (SGR) were evaluated after this experimental period of 28d. Okara supplemented diets did not produce signiﬁcant difference(p<0.05) in the body weight gain FCR and SGR. Okara as a diet supplement had no inﬂuence on feed intake, but the growth rate and feeding efﬁciency were lower in the fermented okara- fed group than in the control group without any detrimental effects on carcass traits. Besides, the proximate composition of fermented okara is also being determined inthis research. The chemical composition revealed that crude protein in the fermented okara which is important for animal is high.